Day‐to‐day variability in the thermosphere and its impact on plasmasphere refilling. Issue 7 (15th July 2016) - Krall, J.; Emmert, J. T.; Sassi, F.; McDonald, S. E.; Huba, J. D.
Abstract: Satellite drag data showing significant (20%) short‐term variations in atmospheric mass density are presented. These data, along with the Naval Research Laboratory SAMI3 (Sami3 is Also a Model of the Ionosphere) ionosphere/plasmasphere model and the WACCM (Whole Atmosphere Community Climate Model) atmosphere model are used to estimate day‐to‐day variability in thermosphere composition, thermosphere winds, and exosphere temperatures and the effect of this variability on plasmasphere refilling rates. This assessment is guided by SAMI3 modeling showing that modest (20%) decreases in thermospheric density and exospheric temperature can lead to large (60%) increases in plasmaspheric refilling rates and that changes in the thermospheric wind pattern can have a similar effect. Results suggest that day‐to‐day variability in thermospheric wind and composition could affect plasmaspheric refilling rates by 50 to 100%. Key Points: Thermosphere composition, temperature, and winds affect plasmasphere refilling rates Orbit data and SAMI3/SD‐WACCM‐X modeling shows day‐to‐day variability in winds and composition The thermosphere produces day‐to‐day variability in plasmasphere refilling rates of 50 to 100%